ANALISIS PENGARUH DANA OTONOMI KHUSUS TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT (Studi Kasus pada Kabupaten/Kota di Provinsi Papua) - Fahrudin, Amanda Anisyah; Susilo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Papua is the easternmost province in Indonesia which is also known as an area with very large natural resources, especially in mining. In addition, Papua Province also holds the title of Special Autonomy for the special nature of Papua which is also followed by the provision of additional transfer funds under the name of the Special Autonomy Fund in its implementation. It has been 20 years since this fund was disbursed, but the welfare situation of the Papuan people is still the lowest in Indonesia. This study aims to see the influence of the Special Autonomy Fund on economic growth and HDI as a proxy for community welfare in regencies/cities in Papua Province. This study used path analysis and maximum likelihood estimation (MLE) using secondary data from DGT Indonesia and BPS Indonesia in the 2011-2020 period. The results of this study are DAK, DBH, PAD and Economic Growth directly affect HDI. Meanwhile, indirectly, the variables that affect HDI are DOK and Adjustment, DAU and PAD.